A prática pedagógica de professoras de uma aluna com deficiência intelectual: desafios e possibilidades no cotidiano de uma escola de ensino fundamental - Costa, Raquel Almeida (2016)
Considering the current principles and objectives of inclusive education, the historical construction of education of people with intellectual disabilities marked by segregation and the teacher's protagonism in the education of these people and in compliance with the principles of inclusion, this research aimed to accomplish a case study to investigate and understand the pedagogical practices of teachers working with a student with intellectual disabilities, in a elementary school of a municipal school in Uberlândia. To achieve this objective, we analyze the teaching practice of four teachers of a student with intellectual disabilities, two teachers from the Support and Educational Service Specialist and two teachers from the Regular Education. We emphasize from the literature the important events in the history of special education and education of people with intellectual disabilities, studies about formation and teacher development and the socio-historical proposals of Vygotsky, theoretical produced that were adopted in the data analysis. We delineate as methodological procedures the qualitative approach, through a case study that examines the pedagogical practices of teachers of a student with intellectual disabilities. For the construction of the data were used as methodological procedures interviews and observations, and to complement the data, document analysis. The data indicated the reflexes of the historical construction of special education and education of people with intellectual disabilities in the pedagogical practice of the teachers, in the characterization of their work routines and their conceptions and perceptions. In addition, it pointed out the limitations of the initial formation for educational work with students with intellectual disabilities and difficulties in realization of continuing education. Finally, the data showed discrepancies between the proposals of socio-historical theory of Vygotsky in certain academic environments, such as the classroom, but congruence in other environments, such as physical education classes.